Upaya Pendidik dalam Menerapkan Nilai Kesopanan Bertingkah Laku pada Peserta Didik di Madrasah Ibtidaiyah Swasta Imam Syafi’i - Haleda, Resni; Nurhayati, Lia; Binggo, Fandi H. (Sahabat Publikasi, 2024)
This research aims to describe how educators make efforts to apply the value of polite behavior to students. this research using qualitative descriptive methods with this research procedure, among others others are observation, interviews, and documentation. As for this research using inductive data analysis through data collection and analysis data, presentation and drawing conclusions. The results of this research show that teachers' efforts to apply the value of polite behavior to students at the Imam Syafi'i Private Madrasah Ibtidaiyah, such as effort to teach always say thank you, provide guidance and advice always say the word sorry, say the word please in the same language good and implementing the 3S and 5S culture, giving sanctions to people who likes to shout and interrupt people's conversations in the form of warnings, advice, etc motivate.